INNOVATIVE TECHNOLOGIES IN THE LITERARY EDUCATION OF FUTURE PRIMARY SCHOOL TEACHERS - Nezhyva, Liudmyla; Palamar, Svitlana (Educological discourse, 2020)
The article substantiates the need for the use of innovative technologies in teaching children’s literature to students majoring in “Primary Education”. The introduction of an integrated course “Native education: children’s literature with studying methods” in the training of future primary school teachers gives them the opportunity to navigate in current trends in children’s literature and model various algorithms of perception and interpretation of the texts. The study analyzes the introduction of interactive technology in literary education, which changes the vector of lectures to dialogic interaction with the student audience, provides a formal update of practical classes using quests and workshops. In accordance with the tasks of the New Ukrainian School and higher education of future primary school teachers, the authors analyze the possibilities of using critical thinking technology, ICT, augmented reality, projects in the system of literary education of the Pedagogical Institute.The importance of acquiring knowledge, skills and abilities to apply AR-applications to interactive editions of fiction by future primary school teachers during their organization of literary reading is substantiated. Tasks with the use of ICT tools have been developed for students. This mainly applies to creation of book trailers and comics based on works of art for children; QR-quests for junior pupils on the texts of fictionsof modern writers; mental maps (Mindmeister resource) based on prose plots; video presentations about writers and their works (resources “PoowToon”, “Prezi”); visualized plan of fictions made with the help of infographics; intellectual game tasks for younger students (LearningApps resource), etc. It was also recognized that the effective type of intellectual activity of students during the study of literature is a project, the result of which is the creation of students’ own literary product (fairy tales, poetry, essays, game content) and its publication in electronic edition.